ANALYSIS AND INVESTIGATION OF SUGAR INDUSTRIAL WASTE WATER - Prof. Bansode S. S; Dr.Nemade P.D.; Mahajan M.P.; Phadtare G.S.; Potphode V.M.; Tupe A.S.; Wable D.M. (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Sugar industries have an important place in Indian Economic Development .However the waste water generates from these industries bear a high degree of pollution load. Waste water from sugar industry, if discharged without treatment, possess pollution problem in both aquatic and terrestrial ecosystems. The rapid growth of the population, the technological and industrial boom has brought enormous problems and degradation of the environment. Effective collection and treatment of urban wastewater is a critical problem in a developing country like India This project work includes Analysis and Investigation of sugar industry waste water by conducting the test such as pH, Temperature, Electrical Conductivity, Turbidity, Dissolve Oxygen (DO), Total Suspended Solid (TSS), Total Dissolve Solid (TDS), Bio Chemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), sulphates . By conducting the following test, we correlate the values of waste water sample.